Archaeological Analysis and Concepts of Causality - Trigger, Bruce G. (Culture, 1982)
The explanatory power of archaeological data is determined by the kind and degree of regularities in socio-cultural phenomena. This paper discusses current anthropological views that are relevant to prehistoric archaeology with respect to four dimensions of freedom or constraint: the role played by rational calculation, the degree of systemic regularity, the relative importance of deterministic foci, and the degree of systemic integration. It is argued that more attention should be paid to this set of problems as part of a broader effort to establish realistic goals for prehistoric archaeology and appropriate methods for achieving them.